PEMANFAATAN LUMPUR IPAL DAN SERBUK GERGAJI MENJADI BRIKET ALTERNATIF - Mohamad Mirwan; Insanul Mufti F (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2020)
Organic materials derived from wood industry waste such as wood sawdust can be used as an alternative source of energy because the calorific value is quite high, which is 4368 cal /g. The purpose of this study is to determine the best characteristics and composition of alternative briquettes. The variables used are briquette composition and different types of adhesive. The results showed that briquettes with the composition ratio of WWTP and Wood Sawdust 1:2 with the addition of adhesive 40% molasses had a heating value of 4185,90 cal/g. Based on Briquettes in this study. The type of test that has not met the quality standard is the compressive strength test of 43.88 kg/cm². These results have not met the quality standards in SNI 4931: 2010 with the classification of type B briquettes with compressive strength test between 50-60 kg/cm².